Детский журнал как средство развития будущего читателя - Lavrukhina O. V., Katkova N. V. (Pedagogical excellence and pedagogical technologies, 2020)
The article is devoted to the problem of children's reading, perception of the text by ear, understanding the meaning and content of the read. Frequent and regular reading, its skillful combination with various types of children's activities contributes to the child's understanding of the world around him, teaches him to feel and love the beautiful, forms the basis of moral qualities of the individual. Reading comprehension and awareness are the main indicators of reading quality. The article considers the children's magazine as an important source of knowledge, which contains literary works (classical and modern), tasks for the development of mental processes, drawings and notes of children, etc. The children's magazine has a great potential for the development of the future reader in the child.
Keywords: художественная литература; fiction; детский журнал; источник знаний; литературные герои; будущий читатель; children's magazine; source of knowledge; literary heroes; future reader